Influence of stock density on turbot (Scophthalmus maximus L.) growth. - Martínez-Tapia, Concha; Fernández-Pato, Carlos (2012)
In this paper the fattening of two groups of turbot (Scophthalmus maximus) under different conditions of stocking densities has been studied. The experience started with 0.25 and 0,50 kg/m2 and lasted with 17 and 68 kg/m2 respectively; periodically, after sampling, t-Student test was applied and no significant differences were shown (p > 0.05), however specific growth and food conversion index show improvement in those fishes stocked in high density respect the other group. Considerations on mortality in case on illness are mentioned. No